Factors Driving World Market Integration: The Case of Jordan’s Industries - Alkhatib, Said; Alkhatib, Alaa (Jordan Journal of Economic Sciences, 2021)
The purpose of this study is to examine the impacts of factors driving world market integration using panel data on the micro-level of 20 industries (2digits-ISIC) over the period 2009-2017. The present study suggested relatively large system of simultaneous equations model to avoid the simultaneous and specification bias. The model consists of three endogenous variables (industrial production, manufactured exports, and manufactured value-added), and four exogenous variables (workers’ compensation, intermediate goods, intermediate services, and spending on improvement and development). Based on the export-to-output ratio, industries have been divided into two groups: the high exporting group (export-to-output ratio exceeds 25%), and the low exporting group (export-to-output ratio varies between 4.5% and 25%). That is to reflect the differences between these two groups which may result due to differences in strategy, competitiveness, innovation, and access to world markets. The simultaneous model was estimated for all industries, and for each of the previous groups. The intermediate goods show very impressive success in most of the equations estimated, confirming the role of imported inputs in driving world market integration in Jordan. The workers’ compensation turn out to have significantly positive effect on most of the endogenous variables for all industries and for the high exporting group. The intermediate services appear to have no significant effect in all models, except for the high exporting group, while spending on improvement and development appears to have a significantly positive effect for the entire sample and for the low exporting group. Finally, the hypothesis of export-led-growth received no empirical support at any significance level in all models.